PENGGUNAAN ALJABAR BOOLEAN DALAM MENGANALISIS KEGAGALAN PADA FAULT TREE ANALYSIS - Mia Fitria; Faisal Faisal (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2009)
System is the dimension which it limited by rule and have certaincharacteristic. Execution of system do not always success, it is caused by somecomponent that causing fault at the system. Minimizing fault can be done bysearching the cause of the fault and then its construct to fault tree. Fault tree is a logic diagram that displays the connection between the fault event and the reason.The connection between the fault event and the reason can be described by ANDgate and OR gate. AND gate is used if all of the input occurs and OR gate is usedif at least one of the inputs occurs. To analyze fault tree, for the first it is changedto Boolean equation where AND gate and OR gate equivalent with product andsum operation in algebra.The methodology of this research is study of literature with search and collectall of the materials that are related with fault tree analysis and Boolean algebraand construct minimal cut set and minimal path set by using the construction offault tree which it is had and search the problem which it is solved by fault treeanalysis.Minimal cut set from a fault tree can be obtained by using Boolean algebra.But, not of all the rules of Boolean algebra are used. It is caused the fault at thedifferent of top event, so that different construction of fault tree for each differentfault. Minimal path set is obtained after getting the complement of minimal cut setwhich it get before and using some rules of Boolean algebra. From minimal cutset can be seen any kind of cause that can make the fault is happened and fromminimal path set can be seen any kind of cause that can make the fault is nothappened. Sum of minimal cut set and minimal path set are not always same foreach fault tree.